Antitumour activity of 3‐nitropropionic acid from Phomopsis sp. and optimization of fermentation conditions. (1st August 2015) - Lu, F.T.; Ma, D.C.; Yan, W.; Guo, J.; Bai, L.H.
Abstract: In this study, 3‐nitropropionic acid (3‐NPA) was separated and purified from endophytic fungi belonging to Phomopsis sp. and its cytotoxicity was determined by MTT assay. Treatment with 3‐NPA for 24 h resulted in a dose‐dependent apoptosis in MCF‐7 cells. Through quantitative detection of the genes that are closely related to the Bcl‐2 signalling pathway, there was an increased expression of p53 and Bax and a decreased expression of Bcl‐2, which indicated apoptosis in these cells. Meanwhile, the overexpression of PARA (poly ADP‐ribose polymerase) and apoptosis inducing factor (AIF) also suggested that 3‐NPA induced cellular apoptosis through a caspase‐3‐independent pathway in caspase‐3‐deficient MCF‐7 cells. The fermentation condition was also improved to produce more 3‐NPA: glucose as a carbon source and yeast extract as a nitrogen source, fermentation for 8 days at 32°C and a solution environment of pH 5·0. Under these conditions, the yield of 3‐NPA was increased to 529 mg l −1 compared with 410 mg l −1 under traditional fermentation conditions. Significance and Impact of the Study: 3‐Nitropropionic acid is a mitochondrial inhibitor and has some useful bioactivities such as antibacterial activity. In this paper we found that 3‐NPA also has obvious cytotoxicity, so we studied its antitumour activity and tried to determine the antitumour molecular mechanism, opening a new perspective for potential antitumour prodrug development. As 3‐NPA is often obtained from natural products with a low yield, in order to overcome the disadvantage of an endophytic fungi source of 3‐NPA, we optimized the fermentation conditions for 3‐NPA in Phomopsis sp. to obtain the maximum production of 3‐NPA.